2015
DOI: 10.5999/aps.2015.42.5.532
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Contracture after Breast Augmentation: An Update for Clinical Practice

Abstract: Capsular contracture is the most common complication following implant based breast surgery and is one of the most common reasons for reoperation. Therefore, it is important to try and understand why this happens, and what can be done to reduce its incidence. A literature search using the MEDLINE database was conducted including search terms 'capsular contracture breast augmentation', 'capsular contracture pathogenesis', 'capsular contracture incidence', and 'capsular contracture management', which yielded 82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
216
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(235 citation statements)
references
References 99 publications
(133 reference statements)
9
216
0
10
Order By: Relevance
“…It is generally believed that the patient's immune system plays a key role in the pathogenesis of capsular fibrosis. Fibroblast, macrophage, and lymphocyte infiltration within the capsule accounts for this reaction [12]. According to previously published reports, fibroblast numbers are increased in accordance with the Baker grade of capsular tissue.…”
Section: Introductionsupporting
confidence: 50%
“…It is generally believed that the patient's immune system plays a key role in the pathogenesis of capsular fibrosis. Fibroblast, macrophage, and lymphocyte infiltration within the capsule accounts for this reaction [12]. According to previously published reports, fibroblast numbers are increased in accordance with the Baker grade of capsular tissue.…”
Section: Introductionsupporting
confidence: 50%
“…In addition to the sample size difference, our measurements did not include the capsular thickness in regions of the implant where a significant overlap was present between the muscle or the surrounding tissue and the capsule. However, we visually observed a distinct difference in the shape of the implant and pectoralis muscles, which led us to investigate the morphologic shape features as a surrogate of CC (18). That investigation demonstrated that a simple measure, such as implant volume, might be insufficient for distinguishing low- from high-grade CC.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 When it occurs, the implant is crumpled or fractured, with visible deformity of the implant and breast. 48,49 In silicone chamber, there also exists a thick capsule around the engineered adipose flap, which has been considered to be a major reason limiting the further expansion of the flap mechanically at a later stage. In our study, lower TGF-β expression at the early stage and reduced capsule formation at the late stage were found in the PCL group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%